Potential of Waste to Energy Processing for Sustainable Tourism in Nusa Penida Island, Bali - Sari, Mega Mutiara; Inoue, Takanobu; Harryes, Regil Kentaurus; Suryawan, I Wayan Koko; Yokota, Kuriko; Notodarmojo, Suprihanto; Priyambada, Ika Bagus; Septiariva, Yenis (Jurnal Bahan Alam Terbarukan, 2021)
Solid waste management on Nusa Penida Island is one of the problems in tourism in Bali Province. To deal with this issue, the government has implemented various policies, where the policy that becomes an essential issue is the processing of energy waste. To support this, it is necessary to study the potential of waste characteristics on the island of Nusa Penida. This study aims to analyse the characteristics of waste on the island of Nusa Penida as an energy source based on the generation and composition of waste. Solid waste generation and composition were measured based on land and marine debris data. The total waste generation on land and marine debris can reach 6364.4 kg/day and 762.8 kg/day, respectively. The waste composition materials consist of masks, plastics, metals, and biodegradable organics with a value of 4.12%, 32.77%, 19.54%, and 43.57%, respectively. Therefore, the potential use of organic biodegradable as solid fuel can reach 51,933.8 MJ/day or 14,426 kWh/day. However, in the thermogravimetric analysis (TGA) test, the residue was 18.6%.